STUDI KASUS: KESULITAN GURU DALAM MENGEMBANGKAN MATERI NORMA PPKN PADA KELAS VI SDN KAWATAN - Ratih Pradhipta Kusuma Hastuti; Jenif Eliya Driatmaja; Isnaini Nur Anisa; Endrise Septiana Rawanoko (JURNAL ILMIAH NUSANTARA, 2026)
Civics Education (PPKn) in elementary schools plays an essential role in instilling values and norms; however, in practice, teachers still encounter various challenges in developing learning materials. This study aims to identify the difficulties faced by teachers in developing norm-related materials in Grade VI Civics learning and to examine their impact on students understanding. The research employed a qualitative approach using a case study design conducted at SDN Kawatan, Surakarta. Data were collected through observations, interviews, and documentation, and analyzed through data collection, reduction, data display, and conclusion drawing and verification. Data validity was ensured through a credibility test using technique and source triangulation. The findings reveal that teachers experience difficulties in designing contextual learning activities, limited learning media and resources, insufficient pedagogical competence, and constrained instructional time. These challenges result in learning that emphasizes memorization, low student engagement, and limited development of students understanding and internalization of norms in their daily lives.